Phytoplankton biodiversity trends in nanobubble aerated shrimp farming at Probolinggo coast, East Java, Indonesia - Noverita Dian Takarina; Suyud Warno Utomo; Lily Susanti; Nurul Taufiqu Rochman; Dedi Cahyadi; Hardi Junaedi; Henry Kasman Hadi Saputra; Rizki Nugraha Saputra (Society for Indonesian Biodiversity, 2020)
Abstract. Takarina ND, Utomo SW, Susanti L, Rochman NT, Cahyadi D, Junaedi H, Saputra HKH, Saputra RN. 2020. Phytoplankton biodiversity trends in nanobubble aerated shrimp farming at Probolinggo coast, East Java, Indonesia. Biodiversitas 21: 5906-5914. Phytoplankton is known as an important factor in shrimp farming and its abundance and biodiversity are varied. Nanobubble aeration is one of current aquaculture treatments used in brackish water shrimp ponds. This study aimed to investigate phytoplankton biodiversity trends in nanobubble and control ponds within 21-day observation period. The measured water quality parameters were dissolved oxygen (DO), NH4+, NO2-, pH, salinity, temperature, and water clarity. Data analysis includes calculation of abundance and biodiversity using Shannon-Wiener (H’) index and correlation using Principal Component Analysis (PCA). A total of 11 phytoplankton species from 5 divisions was recorded. The results show increasing trends in phytoplankton abundance, species, and H’. In pond with nanobubble, H’ increased from 0.322 (95%CI: 0.074-0.718) to 0.561 (95%CI: 0.208-0.916) after 21 days, while in control pond, H’ increased from 0.199 (95%CI: 0.000-0.520) to 0.326 (95%CI: 0.000-0.683). In the nanobubble pond, species showing increasing trend in abundance were Pleurosigma sp., Nitzchia sp., Anabaena sp., Oscillatoria sp., and Microcystis sp. Whereas, species showing a declining abundance trend were Chlorella sp. and Amphora sp. According to PCA, phytoplankton abundance was positively correlated with pH, water clarity, DO, NO2-, and negative correlation with salinity, temperature, and NH4+.